The Effect of Nutrition Education on Nutrition Knowledge and Random Blood Glucose (RBG) in Type 2 Diabetes Mellitus Patients - Nurhalisa Eky Saputri; Siti Uswatun Hasanah; Djunaedi Djunaedi; Icha Dian Nurcahyani (PROMOTOR, 2026)
Background : Diabetes mellitus (DM) is a chronic metabolic disorder characterized by disturbances in insulin secretion and action. Effective management of DM requires optimal blood glucose regulation, in which nutrition education plays a crucial role in enhancing the nutritional knowledge of patients with type 2 diabetes mellitus. Objective : The purpose of this study was to examine the influence of nutrition education on nutritional knowledge and Random Blood Glucose (RBG) levels among patients with type 2 diabetes mellitus in the service area of UPT Turikale Health Center, Maros Regency. Methods : The research design employed a quasi-experimental approach involving 30 respondents who were divided into two groups: an intervention group that received nutrition education through a nutrition booklet, and a control group that did not receive any education. Data were collected using a nutritional knowledge questionnaire and Random Blood Glucose (RBG) examination. Data analysis was performed using an Independent T-test with a significance level of p<0.05. Results : The intervention group showed a significant improvement in nutrition knowledge (p = 0.000), whereas the change in Random Blood Glucose (RBG) levels was not statistically significant (p = 0.701). Nevertheless, a shift in blood glucose categories toward normal levels was observed after the nutritional education. Conclusions : The intervention group demonstrated a significant improvement in nutritional knowledge (p=0.000), while the change in RBG levels was not statistically significant (p=0.701). However, there was a noticeable shift in blood glucose level categories toward the normal range following the nutrition education.